Quantitative estimation of motor fluctuations in Parkinson's disease. (September 2017) - Bonomo, Roberta; Mostile, Giovanni; Raciti, Loredana; Contrafatto, Donatella; Dibilio, Valeria; Luca, Antonina; Sciacca, Giorgia; Cicero, Calogero Edoardo; Vasta, Rosario; Nicoletti, Alessandra; Zappia, Mario
Abstract: Objectives: To provide a quantitative estimation of motor fluctuations in PD through a 12-h Waking-day Motor Assessment (WDMA) and to develop new WDMA-based tools, the Motor Fluctuation Indices. Methods: Two independent samples of PD patients (exploratory population N = 51, testing population N = 109) were examined. Patients underwent a WDMA using the Unified Parkinson's Disease Rating Scale (UPDRS) and were classified as either having or not having motor fluctuations. To quantify motor fluctuations, the Worsening Index (WI), the Mean Fluctuation Index (MFI) and the Coefficient of Variation (CV) were computed. The optimal cut-off for each index distinguishing patients with or without fluctuations was calculated on the exploratory population. Cut-offs' accuracy was then verified in the testing population. Results: Optimal cut-off scores to differentiate stable patients from fluctuating ones were 8.3 for WI, 5 for MFI and 12.9 for CV. Sensitivity and a specificity were 91.2% (95%CI: 85.9 to 96.5) and 87.8% (95%CI: 81.7 to 93.9) for WI; 75% (95%CI: 66.9 to 83.1) and 90.2% (95%CI: 84.7 to 95.8) for MFI; 69.1% (95%CI: 60.4 to 77.8) and 95.1% (95%CI: 91.1 to 99.2) for CV. Patients with a larger magnitude of fluctuation had higher values for all three indices, whereas patients with multiple daily fluctuations presented only higher WI values. Conclusions: WDMA-derived Motor Fluctuation Indices may represent reliable tools for evaluating and quantifying the severity of motor fluctuations in PD patients. Even if WDMA is a time-consuming procedure, the detection of Motor Fluctuation Indices could be helpful in assessing therapeutic efficacy on motor fluctuations. Highlights: A 12-h waking-day motor assessment was performed to PD patients. Motor fluctuation indices were computed to quantify motor fluctuations. Indices accurately differentiated patients with or without motor fluctuation. In fluctuating patients, indices were useful in estimating motor fluctuation severity.